SISTEM INFORMASI GEOGRAFIS PEMETAAN LOKASI BENCANA ALAM DI SUMATERA UTARA BERBASIS WEB - Yustria Handika Siregar; Mardiana Nainggolan ((JurTI) Jurnal Teknologi Informasi, 2018)
Abstract - Developments in information technology, especially information systems have brought convenience that promises a work efficiency. For example geographic information system is a tool with a computer system that is used to map conditions and events that occur on the face of the earth is a system that is helpful in providing and presenting information needed by users. The development especially in the aspect of environmental needs in order to overcome or reduce the impact of disasters in the Sumatran region, and by improving the performance of the BPBD, it is necessary to have a GIS-based information system that can show BPBD disaster points that already exist in North Sumatra. With the existence of map information, especially in the web system, it is expected to provide fast and accurate information, especially knowing the exact location of the disaster. thus facilitating the work of officers in providing disaster information at the head office. Keywords - Geographic Information Systems, Mapping, Web.